Modelling the Spatial Distribution Differences of Compulsory Education Resource - Weihong Liang; Changsong Ma (Discrete Dynamics in Nature and Society)
This paper aimed to explore the difference in the spatial distribution of compulsory education resource allocation. Raw data were collected from the 2020 China Statistical Yearbook (county/district level) and Guangxi Province Statistical Yearbook of China. Data analysis was conducted using the entropy method, comprehensive evaluation method, K-means clusters analysis, analysis of variance, and spatial statistical analysis (Moran’s I index). It was determined that there were significant differences in the spatial distribution of compulsory education. The equilibrium degree to mandatory education resource allocation was divided into three classes: high level, medium level, and low level, and each class presented a spatial aggregation effect in the spatial distribution. Compared with the primary schools, the equilibrium degree of junior secondary school was higher. However, the equilibrium fluctuation of junior secondary schools was more significant among different counties/districts. The equilibrium of educational resources of junior secondary schools in the urban areas was higher than that in the rural areas, but there was no significant difference for the primary school.